2022
DOI: 10.3389/fpubh.2022.907528
|View full text |Cite
|
Sign up to set email alerts
|

Role of an Online Skill-Based Mindfulness Program for Healthcare Worker's Resiliency During the COVID-19 Pandemic: A Mixed-Method Study

Abstract: The COVID-19 pandemic has highlighted the mental health care needs of health care workers. The primary aim of this study was to explore the effects of an online mindfulness program on resiliency in health care workers during the pandemic using a mixed-methods approach. An online 4-week mindfulness program was delivered to healthcare workers (N = 130) in Ontario, Canada. Resiliency was assessed at 3-time points (i.e., pre, post, and 1-month follow-up), and the mindfulness program's efficacy on resiliency was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The Mindfulness Ambassador Program (MAP), developed by the non-profit organization Mindfulness Without Borders, is a structured 12-week, evidence-based group-mindfulness initiative ( 32 34 ). Participants attended weekly one-hour sessions, each focusing on a specific topic and incorporating social and emotional capacity-building practices like inspirational quotes, dialogue prompts, mindfulness exercises, and journaling.…”
Section: Methodsmentioning
confidence: 99%
“…The Mindfulness Ambassador Program (MAP), developed by the non-profit organization Mindfulness Without Borders, is a structured 12-week, evidence-based group-mindfulness initiative ( 32 34 ). Participants attended weekly one-hour sessions, each focusing on a specific topic and incorporating social and emotional capacity-building practices like inspirational quotes, dialogue prompts, mindfulness exercises, and journaling.…”
Section: Methodsmentioning
confidence: 99%
“…During the COVID-19 pandemic, many forms of mindfulness-based practices have gained popularity to reduce psychological stress and anxiety and enhance the sleep quality of healthcare workers (16,17). For example, the online Mindfulness Ambassador Program has increased the resiliency of healthcare workers (16) and mindfulness-based breathing and music therapy have mitigated stress and work-related strain (17). Many mindfulness-based interventions (MBIs) can enhance emotional regulation and reduces symptoms of various mental health disorders (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…19,[25][26][27] Many of the aforementioned studies had small sample sizes, were conducted outside of North America, and started months to over a year after the pandemic onset. Two Canadian psychotherapy studies were identified 20,29 ; 1 measured 2 of the aforementioned symptoms. 20 Research is needed with Canadian HCWs, who face different circumstances related to the nature of their work, health-care systems (funding, universal health care, resources, etc.…”
Section: Introductionmentioning
confidence: 99%